2018
DOI: 10.1007/s00027-018-0586-z
|View full text |Cite
|
Sign up to set email alerts
|

On biogenic turbulence production and mixing from vertically migrating zooplankton in lakes

Abstract: Vertical mixing in lakes is a key driver of transport of ecologically important dissolved constituents, such as oxygen and nutrients. In this study we focus our attention on biomixing, which refers to the contribution of living organisms towards the turbulence and mixing of oceans and lakes. While several studies of biomixing in the ocean have been conducted, no in situ studies exist that assess the turbulence induced by freshwater zooplanktonic organisms under real environmental conditions. Here, turbulence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…Biogenic mixing in the ocean has been widely reported in the literature, but there are only a few studies related to mixing in lakes (Noss & Lorke, 2014;Simoncelli et al, 2017Simoncelli et al, , 2018. The only report of measured values of biogenic dissipation in the lacrustine environment is, as far as we know, the recent study of Sepulveda Steiner et al (2021) who observed a 1 m-thick mixed-layer driven by bioconvection due to vertically migrating bacteria in a stratified lake.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Biogenic mixing in the ocean has been widely reported in the literature, but there are only a few studies related to mixing in lakes (Noss & Lorke, 2014;Simoncelli et al, 2017Simoncelli et al, , 2018. The only report of measured values of biogenic dissipation in the lacrustine environment is, as far as we know, the recent study of Sepulveda Steiner et al (2021) who observed a 1 m-thick mixed-layer driven by bioconvection due to vertically migrating bacteria in a stratified lake.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To assess the effect of turbulence on zooplankton swimming velocity, profiles of temperature fluctuations were acquired at location ''S'' ( Fig. 1) with a Self-Contained Autonomous MicroProfiler (SCAMP), a temperature microstructure profiler, following the sampling procedure in Simoncelli et al (2018). After splitting each profile into 256-point (25 cm) segments, turbulence was assessed in terms of turbulent kinetic energy (TKE) dissipation rates e. Dissipation rates were estimated for each segment using the theoretical spectrum proposed by Batchelor (1959):…”
Section: Turbulence Estimationmentioning
confidence: 99%
“…Recent laboratory studies of millimeter-scale brine shrimp (Artemia salina) aggregations using two-dimensional (2D) flow measurement techniques have shown that induced migrations could generate aggregation-scale mixing eddies through a Kelvin-Helmholtz instability (Wilhelmus and Dabiri, 2014) with effective turbulent diffusivities several orders of magnitude larger than molecular diffusion alone (Houghton et al, 2018;Houghton and Dabiri, 2019). Though the potential for enhanced mixing is substantial, direct measurements of enhanced turbulent dissipation and mixing in lakes and the ocean due to vertical migrations have been less conclusive (Noss and Lorke, 2014;Simoncelli et al, 2018;Kunze, 2019). Parameterizing the precise conditions and mechanisms that lead to enhanced mixing remains an active area of research Ardekani, 2012, 2015;Ouillon et al, 2020;More and Ardekani, 2021).…”
mentioning
confidence: 99%